HUBUNGAN ASUPAN ZAT BESI DAN KALSIUM DENGAN KEJADIAN DISMENORE PADA REMAJA PUTRI - Desi Wildayani; Widya Lestari; Winda Listia Ningsih (JOMIS (Journal of Midwifery Science), 2023)
One sign of reproductive maturity in young women is the arrival of menstruation or menstruation (menarche). A common menstrual disorder is painful menstruation (dysmenorrhea), especially during adolescence. The incidence of dysmenorrhea in the world is quite high. The prevalence of menstrual pain in Indonesia consists of 54.89% primary dysmenorrhea and 9.36% secondary dysmenorrhea. If left untreated, dysmenorrhea can develop into pathological conditions, including infertility. Dysmenorrhea that every woman experiences is different, some are a little annoying, but some are unable to carry out activities. Many nutrients, such as magnesium, calcium, vitamin E, and iron, have also been linked to dysmenorrhea. Adequate intake of calcium and iron is believed to reduce dysmenorrhea. The purpose of this study was to determine the relationship between intake of iron and calcium with the incidence of dysmenorrhea in young women at SMP Negeri 16 Padang. This research uses observational analytic method with cross sectional design. The sample in this study were 39 young women (grade IX students) using a proportional random sampling technique. Researchers used a menstrual questionnaire and a 24-hour food recall form. This research was conducted from July to September 2022. The research results were processed using the chi square statistical test. From a study conducted on 39 respondents, it was found that most respondents (61.5%) experienced dysmenorrhea, 30.8% of respondents had insufficient iron intake and most (87.2%) had calcium intake that was less than the adequacy rate. daily minimum nutrition. The results of the bivariate test found that there was no relationship between iron (Fe) intake and the incidence of dysmenorrhea (p value 0.083) and there was no relationship between calcium intake and the incidence of dysmenorrhea in young women at SMPN 16 Padang with p value = 0.062. Adolescent girls should still pay attention to iron and calcium intake in their daily consumption because if the intake is insufficient it can increas.e the risk of dysmenorrhea.